How to do things with questions: the role of patients' questions in Short-Term Psychoanalytic Psychotherapy (STPP) with depressed adolescents. Issue 1 (2nd January 2022) - Yadlin, Yael; Edginton, Elizabeth; Lepper, Georgia; Midgley, Nick
ABSTRACT: The role of patients' questions in psychoanalytic psychotherapy is a neglected topic in the clinical and research literature. This qualitative study aims to bridge this gap by exploring the role of patients' questions in Short-Term Psychoanalytic Psychotherapy (STPP) with adolescents suffering from depression. This is a single case study, focusing on the interaction between the patient and his therapist when questions were asked by the patient, using conversation analysis methodology. Data was taken from the IMPACT study, a randomised controlled trial, investigating three types of therapy in the treatment of adolescent depression. The findings identify some typical ways in which the therapist responded to the patient's questions, and show that 'surprising behaviours' that seem associated with heightened affect appeared when the patient asked a question, leading to an enlivening of the therapeutic interaction. The study examines the significance of these findings within the context of the therapeutic relationship and discusses the implication of these findings for technique.